Dosis Pupuk NPK Terhadap Pertumbuhan dan Hasil Jagung Hibrida - Pricillia Galuh Pusparini; Ahmad Yunus; Dwi Harjoko (Agrosains : Jurnal Penelitian Agronomi, 2018)
Corn is an important crop. Potency of corn productivity in Indonesia are still low. Main obstacles of increasing corn productivity is convertion of fertile land into non agriculture interest. the increase of corn productivity can be done by administrating NPK fertilizer and hybrid variety. This research is aiming at deciding and analyzing the effect of NPK fertilizer administration and hybrid corn variety towards growth and result. This research was held in June to October 2017, at Srimartani Village, Piyungan Districts, Bantul Regency, Daerah Istimewa Yogyakarta with regosol soil type and land altitude around 80 meter above sea surface. This experiment arranged in split plot design by factorial. Experimented factor are two corn hybrid variety ABCD and EFGH (main plot) with three doses of NPK fertilizer 200, 300 and 400 kg ha-1 (sub plot). The result of research show that there are responds in two variety towards NPK fertilizer dosage almost same (unreal interraction). ABCD and EFGH variety reach highest result of height and component at 300 kg ha-1doses. Variable of cob weight with husk, cob weight without husk, cob length, total row, dry pipilan weight per plot, 100 seeds weight, fresh stover wieght, dry stover weight, harvest index and yield per hectare the highest average is variety of EFGH. NPK fertilizer dosage 300 kg ha-1 is the best amount to optimally increase the growth and yield of hybird corn (8,92 ton ha-1). EFGH variety with 300 kg ha-1 NPK fertilizer dosage can increase the potency of hybird corn yield. EFGH variety is showing better results (9,26 ton ha-1).